Claims-making about the battered woman syndrome in expert testimony and news media: The case of R v Getkate - Rossiter, Katherine R (University of Ottawa (Canada), 2005)
This study examines claims-making about the Battered Woman Syndrome (BWS) in the case of Lilian Getkate, who used the syndrome to substantiate a claim of self-defence after killing her abusive husband. The research is guided by the social constructionist perspective and employs content analysis to determine what claims are made in expert testimony and news media about the BWS. It examines how this construct is linked to the defendant and what claims are made about the criminal justice system's response to intimate partner violence and homicide. This research also considers the claims-makers themselves and claims regarding their expertise. Findings from this in-depth case study reveal the importance of expertise and credentials in claims-making and suggest that claims about the BWS, its relation to the defendant, and the law's response are constructed in similar ways in expert testimony and news media, though much more developed in the former.
Keywords: Sociology, Criminology and Penology.